The study of genetic predictors of age at natural menopause. A literature review - Szwejser, Ewa; Marczakiewicz, Anna (Menopause Review/Przegląd Menopauzalny, 2012)
In light of the increased life expectancy of the population associated with the development of modern medicine, health-related information and socioeconomic conditions, more and more researchers are focused on health problems related to the late adulthood, and menopause. The age of menopause appearance may be an indicator of the biological condition of the population. It also might be a determinant of the risk of incidence of diseases such as osteoporosis, breast or genital cancers. Prediction of the reproductive period’s length in the individual cases may be very important for family planning and infertility treatment. Currently, there are numerous studies devoted to the analysis of the environmental and biological factors of natural menopause. However, they do not explain the whole spectrum of diversity of this phenomenon. The interaction of genetic, biological and environmental factors decide when menopause occurs. A huge development of research regarding the identification of genes responsible for natural menopause age has been observed in the last decade. This article provides an overview of research about genetic markers of menopause. In the studies devoted to this issue, we can distinguish three basic methods: genome-wide linkage analysis, candidate gene association studies, and genome-wide association studies - GWAS. In this article we describe the applicability, limitations and test results as well as the usage of these methods.